Scopolamine 유발 기억 손상 마우스에서 익모초의 효과 - 이지혜(Jihye Lee); 김혜정(Hye-Jeong Kim); 장귀영(Gwi Yeong Jang); 서경혜(Kyung Hye Seo); 김미려(Mi Ryeo Kim); 최윤희(Yun Hee Choi); 정지욱(Ji Wook Jung) (동의생리병리학회지, 2020)
Cognitive impairment is symptoms of dementia, a degenerative brain disease that is drawing attention in a rapidly aging society. This study was conducted to investigate the improvement of cognitive function of Leonurus japonicus on scopolamine-induced memory impairment in mice and the effect and mechanism of memory recovery. In vivo studies were conducted on mice orally pretreated with L. japonicus in doses of 50, 100 and 200 mg/kg (p.o.) and scopolamine (1 mg/kg, i.p.) were injected 30 min before the behavioral task. Antioxidant activity was assessed by 2,2-diphenyl-1-picryl hydrazyl (DPPH) assay and 2,2-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assay, and acetylcholinesterase (AChE) inhibition activity evaluated by Ellman's method. In behavior studies showed that L. japonicus has an improved the memory of scopolamine-treated mice in Y-maze, passive avoidance and Morris water maze test. In addition, L. japonicus was also exerted free radical scavenging activity and inhibited acetyl cholinesterase activity. These results suggest that L. japonicus improves short-term and long-term memory in scopolamine-induced memory decline model and prevents scopolamine-induced memory impairments through in reduced oxidative stress and acetyl cholinesterase inhibition effect. Thus, L. japonicus is related to functional medicinal materials for prevention and treatment of human dementia patients.